Ketidakadilan Gender dan Strategi Bertahan Perempuan dalam Cantik Itu Luka karya Eka Kurniawan - Nurhasanah, Siti; Indriyani, Iin; Haryadi, Ardi Mulyana; Alsunah, Aditya Ansor (eScience Humanity Journal, 2025)
Literary works function not only as aesthetic expressions but also as reflections of social realities, including issues of gender inequality. This study examines gender injustice and women’s survival strategies in Cantik Itu Luka by Eka Kurniawan, with a particular focus on the character of Dewi Ayu as the central figure. The research aims to identify the forms of gender-based injustice experienced by the female protagonist and to analyze her strategies for survival within the context of colonial patriarchy. Employing a qualitative descriptive method, this study applies feminist criticism and a sociological literary approach. Data were collected through library research and close textual analysis of relevant narrative excerpts, which were then interpreted critically. The findings reveal that Dewi Ayu experiences multiple forms of gender injustice, including negative stereotyping, sexual violence, physical and emotional abuse, and the objectification of the female body within a patriarchal colonial system. Rather than portraying resistance through overt physical rebellion, the novel represents the protagonist’s struggle through survival strategies such as bodily negotiation and endurance in oppressive circumstances. This study concludes that Cantik Itu Luka portrays women as subjects who endure layered oppression while simultaneously articulating a strong social critique of patriarchal domination.